Analisis Atraksi Wisata dan Fasilitas Wisata Di Pantai Despan Kecamatan Natal Kabupaten Mandailing Natal - Ayu, Bunga Sukma; Susanti, Retnaningtyas (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
This research was motivated by several problematic facts found in tourist attractions and tourist facilities at Despan Beach, Natal District, Mandailing Natal Regency. Tourist attractions at Despan Beach are not yet varied. Facilities at Despan Beach are also inadequate, such as public toilet facilities, parking lots, rubbish bins, road access is not representative. Lack of supporting facilities such as photo spots in the Despan Beach area, Natal District, Mandailing Natal Regency. The general research purpose is to analyze tourist attractions and tourist facilities at Despan Beach, Natal District, Mandailing Natal Regency based on indicators of natural attraction, built attraction, cultural attraction and accessibility, accommodation, amenities, attractions, activities, information & tourist guides, security and health, cleanliness, supporting facilities and a comfortable environment. This research type included in descriptive through qualitative data. The technique for informant selection used was purposive sampling. The research informants were the Mandailing Natal Regency Tourism Office, the Despan Beach Management, the people who sell around Despan Beach and Despan Beach Visitors. The techniques for data collection are observation, documentation and interviews. The techniques for data analysis used are data reduction, data presentation and conclusion drawing.                 Based on the research results, researchers found several analyzes of tourist attractions at Despan Beach, Natal District, Mandailing Natal Regency, namely: 1). Natural Attraction at the front beach in the shape of natural scenery in the shape of a beach 2). Built Attraction is not yet available at Despan Beach 3).Cultural Attraction is not yet available at Despan Beach. Researchers also found several analyzes of tourist facilities at Despan Beach, Natal District, Mandailing Natal Regency 1). Accessibility at the front beach is currently at an adequate level as shown from the access road to the beach 2). Accommodation at Despan Beach is easily accessible to visitors where there is a mess/lodging only 100 meters from Beach 3). The amenities available in this beach area are quite good and adequate, namely in the form of a café which is area right on the edge of the beach 4). The attractions at Despan Beach are not yet varied, visitors can only see natural tourist attractions in the form of beautiful beach views 5) Activities that can be done at Despan Beach are currently very limited, namely only trying various types of food around the beach 6). Information & tour guides at Despan Beach are not yet available 7). Security and health at Despan Beach are very good and well maintained 8). Cleanliness at Despan Beach has not been maintained properly, there is still a lot of rubbish scattered along the beach 9). The special supporting facilities at Despan Beach are in good condition where there is an ATM which is around 700 m from the beach. 10) The comfortable environment at Despan Beach is quite well established, seen from the existing accessibility provisions and there are lodging places close by.